Eph/ephrin Function Contributes to the Patterning of Spinocerebellar Mossy Fibers Into Parasagittal Zones - Lackey, Elizabeth P.; Sillitoe, Roy V. (Frontiers in Systems Neuroscience, 2020)
Purkinje cell microcircuits perform diverse functions using widespread inputs from the brain and spinal cord. The formation of these functional circuits depends on developmental programs and molecular pathways that organize mossy fiber afferents from different sources into a complex and precisely patterned map within the granular layer of the cerebellum. During development, Purkinje cell zonal patterns are thought to guide mossy fiber terminals into zones. However, the molecular mechanisms that mediate this process remain unclear. Here, we used knockout mice to test whether Eph/ephrin signaling controls Purkinje cell-mossy fiber interactions during cerebellar circuit formation. Loss of ephrin-A2 and ephrin-A5 disrupted the patterning of spinocerebellar terminals into discrete zones. Zone territories in the granular layer that normally have limited spinocerebellar input contained ectopic terminals in ephrin-A2-/-;ephrin-A5-/- double knockout mice. However, the overall morphology of the cerebellum, lobule position, and Purkinje cell zonal patterns developed normally in the ephrin-A2-/-;ephrin-A5-/- mutant mice. This work suggests that communication between Purkinje cell zones and mossy fibers during postnatal development allows contact-dependent molecular cues to sharpen the innervation of sensory afferents into functional zones.